Feasibility of incorporating phosphogypsum in ettringite-based binder from ladle slag. (10th November 2019) - Gijbels, Katrijn; Nguyen, Hoang; Kinnunen, Paivo; Schroeyers, Wouter; Pontikes, Yiannis; Schreurs, Sonja; Illikainen, Mirja
Abstract: Aiming to utilize phosphogypsum (PG) as a construction material, this study investigated the potential use of PG as a calcium sulfate source for the production of an ettringite-based binder (LSG). Six compositions with different percentages and PG's of different origin were hydrated with ladle slag (LS) to form LSG. The hydration, mineralogy and compressive strength of all mixtures were investigated and compared with a reference LSG made of pure synthetic gypsum. The minor impurities in PG, the different particle size distribution as well as the mineralogy induced distinguishable effects on the heat of hydration, phase assemblage and morphology. The results showed that the use of side-stream PG instead of pure gypsum results in superior properties with a 60% increase in compressive strength. This investigation shows high potential to produce a completely by-product-based LSG by combining different sources of industrial side-streams with minimal chemical and energy use. Highlights: Various sources of phosphogypsum were incorporated in an ettringite-based binder. The impurities in phosphogypsum delayed the setting of the developed binders. Polish phosphogypsum led to an increase of 60% in compressive strength. Ettringite-based binders can be produced entirely from industrial side-streams.